ARTIFICIAL INTELLIGENCE IN ACCOUNTING: A NEW REALITY - Zarina Berdimuratova (TADQIQOTLAR, 2025)
This article explores the impact of artificial intelligence (AI) on modern accounting practices. The key areas of AI application in accounting, financial control, and cash flow management are analyzed. Special focus is placed on automation, intelligent data analytics, and financial risk forecasting. The study substantiates the transformation of the accountant’s role under the conditions of digital economic development.